Dramatic Structure Strategies in the Creation of Children's Short Drama Scripts Based on Jambi’s Traditional Games Collections in Museum Siginjei - Santoso, Ady; Leihitu, Irsyad; Utama, Galuh Tulus (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2023)
Traditional games are one of the ten Objects of Cultural Advancement, which are essential to maintain, utilize, and innovate to maintain and pass them on to the next generation. The collection of Jambi traditional games at the Museum Siginjei Jambi is vital to continue to be preserved and passed on in innovative forms. One form of innovation is using a collection of Jambi’s Traditional Games as a source for creating children's short drama scripts. This research looks for dramatic structure strategies for creating short children's drama scripts based on five collections of Jambi’s Traditional Games at the Museum Siginjei Jambi. The qualitative interpretative approach is applied to interpret the data obtained according to the researcher's point of view and understanding. As a result of the dramatic structure strategy in creating five children's short drama scripts, it was found that the strategy applied was a strategy of repeating the same dramatic ladder structure from the beginning, the rise of the problem, the peak of the problem, to the resolution of the problem in each short children's drama script created. Abstrak Permainan tradisional adalah satu dari sepuluh Objek Pemajuan Kebudayaan, yang menjadi penting untuk dipertahankan, dimanfaatkan, dan dilakukan inovasi dalam upaya pemeliharaan, pewarisan kepada generasi berikutnya. Koleksi permainan tradisional Jambi di Museum Siginjei Jambi penting untuk terus dilestarikan dan diwariskan dalam bentuk yang inovatif. Salah salah satu bentuk inovasi yang dapat diterapkan dengan menjadikan koleksi permainan tradisional Jambi sebagai sumber penciptaan naskah drama pendek anak. Penelitian ini untuk mencari strategi struktur dramatik guna penciptaan naskah drama pendek anak yang bersumberkan lima koleksi permainan tradisional Jambi di Museum Siginjei Jambi. Metode kualitatif pendekatan interpretatif diterapkan guna menafsirkan hasil data yang diperoleh sesuai sudut pandang dan pemahaman peneliti. Hasilnya strategi struktur dramatik dalam menciptakan lima naskah drama pendek anak didapatilah bahwa strategi yang diterapkan adalah strategi pengulangan struktur tangga dramatik yang sama dari permulaan, tanjakan permasalahan, puncak permasalahan, hingga penyelesaian permasalahan di setiap naskah drama pendek anak yang diciptakan.